Anti-leakage liquid metal / melamine insulating heat-conducting film and preparation method thereof

By combining composite modified melamine sponge with liquid metal in gallium indium alloy, combined with ultrasonic treatment and mechanical sintering technology, a liquid metal/melamine insulating thermal conductivity film is formed, which solves the problem of difficult balance between leakage and thermal conductivity and flexibility of liquid metal-based thermal conductivity composite materials in the prior art, and achieves efficient thermal conductivity and insulation properties.

CN119823443AActive Publication Date: 2025-04-15SICHUAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510053130.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

Existing liquid metal-based thermally conductive composite materials are prone to leakage problems under high filling, and it is difficult to balance between thermal conductivity and flexibility, especially in complex scenarios where insulation performance is required.

Method used

Gallium indium alloy is used as liquid metal, and the combination of composite modified melamine sponge and liquid metal is combined with liquid metal, and ultrasonic treatment and mechanical sintering technology is used to form a leakage-proof liquid metal/melamine insulating thermal conductive film. The film forms a micron-thick liquid metal film through multiple impregnation and sintering processes, and covers the surface with a PDMS protective layer to enhance insulation and leak resistance.

Benefits of technology

It achieves improved thermal conductivity and flexibility without leaking liquid metal, meets insulation and thermal conductivity requirements in complex scenarios, and shows excellent fatigue resistance in multiple cycle deformation tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823443A_ABST
    Figure CN119823443A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-leakage liquid metal / melamine insulating heat-conducting film and a preparation method thereof, and relates to the technical field of high polymer materials. (1) sponge matrix selection: the selected matrix is composite modified sponge; (2) liquid metal selection; (3) preparing liquid metal / ethanol dispersion liquid; (4) melamine sponge dipping treatment; (5) drying treatment; (6) dipping for multiple times; (7) pressing liquid metal components; (8) preparing a PDMS / ethyl acetate solution; and (9) forming. The composite modified sponge disclosed by the invention has a relatively large pore diameter and a rich three-dimensional network structure, so that the composite modified sponge has extremely low density and excellent flexibility, the sponge subjected to composite modification treatment has higher intrinsic thermal conductivity, and the adsorption effect on liquid metal is also obviously improved. Due to the extremely high porosity of the composite sponge and the acting force between the composite sponge and the liquid metal, the composite sponge can bear the filler filling amount of 60 vol% or above without leakage, and the PMDS coating layer provides the insulation performance for the composite material and further enhances the leakage-proof performance of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular to a leakage-proof liquid metal / melamine insulating heat-conductive film and a preparation method thereof. Background Art

[0002] Thermal interface materials are currently widely used in various electronic and electrical equipment that require efficient thermal management. Their main function is to fill the interface gap and reduce the contact thermal resistance, thereby improving the heat dissipation capacity of the equipment and ensuring the thermal stability and reliability of the equipment. Traditional thermal conductive composite materials are generally based on metal materials and carbon materials. Although they have high thermal conductivity, the fillers are rigid particles. At low filling amounts, the fillers cannot build a dense and effective thermal conductive network in the matrix, which limits the improvement of the thermal conductivity of the composite materials. When the filling amount is too high, it is often accompanied by a significant decrease in mechanical properties. In the interface of complex structures, it shows insufficient flexibility or unstable compression performance, and it is difficult to fully fill the microscopic gaps, making it difficult to exert the thermal conductivity of the composite material. The disordered arrangement of fillers in the composite material also greatly reduces its utilization rate. In some special scenarios (such as new energy vehicle battery modules), the material needs to have excellent thermal conductivity and meet specific electrical insulation requirements. It is difficult for traditional composite materials to achieve a balance in these aspects.

[0003] As an emerging material, liquid metal has opened up a new path for the innovative design of flexible composite materials with its unique physical state - liquid at room temperature and high thermal conductivity (>16.5 W / m·K). The fluidity of liquid metal enables it to penetrate into the internal structure of the composite material, forming a stable and efficient thermal conduction path.

[0004] Melamine sponge is made of melamine. Its flexibility makes it an excellent choice as a thermal interface material matrix. Its fine and rich three-dimensional mesh structure and large pore size enable it to effectively carry a higher content of liquid metal, thereby forming an efficient heat conduction network while avoiding liquid metal leakage. Melamine sponge has good processing properties and can be made into accessories of various shapes and sizes through molding and other processes to adapt to various complex application scenarios.

[0005] The Chinese patent with publication number CN114940829B discloses a two-dimensional graphene / liquid metal / PDMS composite film and its preparation method. This invention uses a photosensitive resin as a skeleton, fills PDMS and then demolds to obtain a flexible PDMS matrix, which can give the filler a thermal conductivity path, thereby improving thermal conductivity. However, this method fills too much PDMS, which inhibits the improvement of thermal conductivity. Although it can give the composite material a certain flexibility, it is easy to block the thermal conductivity path under mechanical deformation and produce the risk of liquid metal leakage.

[0006] The Chinese patent application number CN202210597791.5 discloses a composite high thermal conductivity interlayer gasket based on liquid metal filling and its preparation method, but the hardness of this composite material is still high, it is not flexible, and the thermal conductivity is less than 5 / W·m -1 ·K -1 , cannot meet the thermal conductivity requirements in complex scenarios.

[0007] The existing preparation methods of liquid metal-based thermally conductive composite materials have leakage problems caused by high filling and the contradiction between high thermal conductivity and flexibility of thermally conductive composite materials. At the same time, good insulation performance needs to be ensured in specific scenarios. Based on this, the present invention provides a leakage-proof liquid metal / melamine insulating thermally conductive film and a preparation method thereof to solve the existing technical problems. Summary of the invention

[0008] The purpose of the present invention is to provide a leakage-proof liquid metal / melamine insulating thermally conductive film and a preparation method thereof, so as to solve the deficiencies in the prior art.

[0009] The technical solution adopted by the present invention is as follows: A method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film, the preparation method comprising the following steps: (1) Sponge matrix selection: The selected matrix is ​​a composite modified sponge; (2) Liquid metal selection: Gallium-Indium alloy; (3) Preparation of liquid metal / ethanol dispersion: mixing liquid metal and ethanol, and then placing them in an ultrasonic cell crusher for crushing to obtain a liquid metal / ethanol dispersion; The mass ratio of liquid metal to ethanol is 1:12-1:18, the ultrasonic power is 400W, and the treatment time is 2-6min; (4) Melamine sponge impregnation treatment: the composite modified sponge obtained in step (1) is placed in the liquid metal / ethanol dispersion obtained in step (3) at a volume ratio of 1:5 for impregnation treatment, and then taken out to obtain an impregnated sample; (5) Drying: Place the vacuum impregnation sample obtained in step (4) into a forced air drying oven for drying until the ethanol is completely evaporated; Among them, the wind speed in the blast drying oven is 0.5m / s, the temperature is 50℃, and the time is 0.5 hours; (6) Multiple impregnation: repeating steps (4) and (5) multiple times to obtain a multiple impregnation composite material; (7) Sintering the liquid metal component: mechanically sintering the multiple impregnation composite material obtained in step (6) to obtain a film sample; (8) Preparation of PDMS / ethyl acetate solution: PDMS: curing agent in a mass ratio of 9:1 were mixed evenly to obtain a preliminary mixture, and the preliminary mixture: ethyl acetate was poured into a centrifuge tube in a mass ratio of 1:9, and centrifuged and stirred for 5 minutes to prepare a 10% PDMS / ethyl acetate solution. The obtained solution was diluted 10 times to obtain a 1% PDMS / ethyl acetate solution; (9) Molding: The film sample obtained in step (7) is suspended on an aluminum mesh support to reduce the contact between the liquid metal and the support; the 1% PDMS / ethyl acetate solution obtained in step (8) is taken with a pipette and dripped onto both sides of the film sample to evenly cover the film sample, and the film sample is placed in an air drying oven to evaporate the ethyl acetate, thereby finally obtaining a leak-proof liquid metal / melamine insulating thermal conductive film; The air velocity in the blast drying box is 0.5 m / s, the temperature is 60° C., and the time is 2 hours.

[0010] As a further technical solution, the density of the selected composite modified sponge is 0.0080-0.0085 g / cm 3 , thickness is 0.4~0.6cm.

[0011] As a further technical solution, the curing agent in step (8) is tetraoxetane disulfide; As a further technical solution, the method for preparing the composite modified sponge comprises the following steps: (1) The melamine sponge was repeatedly rinsed with anhydrous ethanol and deionized water for 10 minutes, and then vacuum dried at 55°C for 2 hours to obtain a cleaned melamine sponge; (2) The silver nanowires are uniformly dispersed in deionized water to obtain a silver nanowire dispersion.

[0012] (3) immersing the cleaned melamine sponge in the silver nanowire dispersion, applying a pressure of 0.5 MPa to the cleaned melamine sponge, maintaining the pressure for 10 seconds, then releasing the pressure and maintaining it for 20 seconds, repeating the cycle for 5 times, then taking it out, placing it in a vacuum drying oven at 55° C. and vacuum drying it for 4 hours to obtain a melamine sponge composite material; (4) adding dopamine hydrochloride to the Tris solution, stirring and mixing to obtain a treatment solution; The melamine sponge composite material was added to the treatment liquid, ultrasonically dispersed for 10 minutes, the temperature was adjusted to 65°C, and after being sealed and immersed for 15 hours, it was taken out and then vacuum dried at 55°C for 4 hours to obtain a composite modified sponge.

[0013] As a further technical solution, the mass fraction of silver nanowires in the silver nanowire dispersion is 10-13wt%; The cleaning melamine sponge is immersed in the silver nanowire dispersion at a volume ratio of 1:10; The mixing ratio of dopamine hydrochloride and Tris solution is 1-1.2 g: 120 mL; The volume ratio of melamine sponge composite material and treatment liquid is 1:5.

[0014] As a further technical solution, the gallium-indium alloy has a mass fraction of gallium of 75.5% and a mass fraction of indium of 24.5%.

[0015] As a further technical solution, the vacuum impregnation time is 4-5 hours, the vacuum degree is 0.1 Pa, and the temperature is 70°C.

[0016] As a further technical solution, the multiple repetitions of steps (4) and (5) are specifically repeated 1 to 4 times.

[0017] As a further technical solution, the mechanical sintering step is: divide the obtained multi-impregnation composite material into four parts, put them into a tablet press for automatic pressing, each time the tablet press acts on one of the four parts, four times as a cycle, and a total of 10 to 12 cycles.

[0018] It should be noted that the mechanical sintering in the present invention is not high-temperature sintering in the traditional sense, but a process of bonding liquid metals by applying pressure at room temperature, i.e., mechanical sintering. This mechanical sintering is a solid-state connection technology that does not rely on the traditional high-temperature sintering process, but achieves connection between materials by applying external pressure.

[0019] As a further technical solution, the pressing pressure is 1 MPa and the pressing time is 2 s / time.

[0020] As a further technical solution, the dripping amount on both sides of the film sample in step (9) is 20 μL / cm² respectively. Beneficial Effects

[0021] 1. Melamine sponge is mainly composed of melamine resin, and its surface chemical properties are weakly compatible with liquid metal. It is mainly combined through physical intercalation and weak van der Waals force, and the binding energy is low. The present invention performs a composite modification on the melamine sponge matrix and introduces silver nanowires for combination. Silver nanowires have a higher free electron density and may produce a stronger interaction with the surface electron cloud of liquid metal. In addition, gallium in liquid metal can usually form a stable gallium oxide film. This oxide layer can be combined with the silver surface on the metal surface through van der Waals force or chemical bond to obtain a higher binding energy, thereby making the composite modified melamine sponge have a higher adsorption capacity for liquid metal.

[0022] 2. The present invention immerses the modified melamine sponge in a liquid metal / ethanol dispersion. The liquid metal in the dispersion fully penetrates and fills the pores of the modified melamine sponge through capillary action, forming a good physical bond. At the same time, the liquid metal has a high surface tension, and will automatically shrink in the pores and adhere to the surface of the pore wall. During the blast drying, the increase in temperature causes the liquid metal to flow further, fully covering the pore wall of the melamine sponge, further enhancing its adhesion. In the subsequent partial sintering process, the liquid metal fills the gaps due to the compression of the gaps, and the excess part flows to the edge. After multiple cycles, a liquid metal film with a thickness of micrometers is finally formed. The liquid metal changes from a small droplet attached to the skeleton to a sheet after sintering and fills the inside of the film.

[0023] Since the binding force between liquid metals is mainly determined by surface tension, and the skeleton of melamine sponge is extremely thin, its resilience is much smaller than the binding force between liquid metals, so the film will not return to a porous sponge state after formation. After the liquid metal inside the film is cleaned with anhydrous ethanol, the film can rebound to a porous sponge state, which also proves that the present invention does not achieve the effect of non-rebound by permanently destroying the skeleton of melamine sponge, but uses the difference between the binding force between liquid metals and the resilience of melamine sponge to achieve stability control of film morphology.

[0024] 3. The present invention controls the average particle size of the liquid metal particles in the liquid metal / ethanol dispersion by using specific ultrasonic time and ultrasonic power. Under this average particle size, the degree of bonding between the liquid metal and the melamine sponge is the highest, which is most advantageous for the molding of the material.

[0025] 4. The present invention also forms a micron-level protective layer on the surface of the film through the use of PDMS, which further prevents the leakage of liquid metal without changing the overall morphology too much, and also provides effective insulation performance, and significantly improves the flexibility and durability of the material, and can maintain stable mechanical properties in a wide temperature range of 20°C to 150°C. Especially in multiple cyclic deformation (such as bending, compression) tests, after more than 1,000 cycles, its mechanical properties, insulation properties and thermal conductivity properties have no obvious attenuation, reflecting excellent anti-fatigue performance.

[0026] 5. The present invention has simple production process, low cost, good performance and can be produced in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Attached Figure 1 This is the scanning electron microscopy of the liquid metal / ethanol dispersion when the ultrasonic time is 2 minutes in Example 6; Attached Figure 2 This is a scanning electron microscope image of the liquid metal / ethanol dispersion when the ultrasonic time is 4 minutes in Example 1; Attached Figure 3This is a cross-sectional scanning electron microscope of the thermally conductive film prepared in Comparative Example 4; Attached Figure 4 This is a scanning electron microscope image of Example 5 after the surface is coated with PDMS; Attached Figure 5 It is a schematic diagram of Example 5 under pressures of 100, 300, and 500 kPa.

[0028] Attached Figure 6 It is a schematic diagram of the process flow of the preparation method of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The following are specific embodiments: Example 1

[0031] A method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film, the preparation method comprising the following steps: (1) Sponge matrix selection: The selected matrix is ​​a composite modified sponge; (2) Liquid metal selection: Gallium-Indium alloy; (3) Preparation of liquid metal / ethanol dispersion: mixing liquid metal and ethanol, and then placing them in an ultrasonic cell crusher for crushing to obtain a liquid metal / ethanol dispersion; The mass ratio of liquid metal to ethanol was 1:12, the ultrasonic power was 400 W, and the treatment time was 4 min; (4) Melamine sponge impregnation treatment: the composite modified sponge obtained in step (1) is placed in the liquid metal / ethanol dispersion obtained in step (3) at a volume ratio of 1:5 for impregnation treatment, and then taken out to obtain an impregnated sample; (5) Drying: Place the impregnated sample obtained in step (4) into a forced air drying oven for drying until the ethanol is completely evaporated; Among them, the wind speed in the blast drying oven is 0.5m / s, the temperature is 50℃, and the time is 0.5 hours; (6) Multiple impregnation: In this embodiment, steps (4) and (5) are not repeated to obtain an impregnated composite material; (7) Sintering the liquid metal component: mechanically sintering the multiple impregnation composite material obtained in step (6) to obtain a film sample; (8) Preparation of PDMS / ethyl acetate solution: PDMS: curing agent in a mass ratio of 9:1 were mixed evenly to obtain a preliminary mixture, and the preliminary mixture: ethyl acetate was poured into a centrifuge tube in a mass ratio of 1:9, and centrifuged and stirred for 5 minutes to prepare a 10% PDMS / ethyl acetate solution. The obtained solution was diluted 10 times to obtain a 1% PDMS / ethyl acetate solution; The curing agent is tetraoxetane disulfide; (9) Suspending the film sample obtained in step (7) on an aluminum mesh support to reduce the contact between the liquid metal and the support; using a pipette to absorb the 1% PDMS / ethyl acetate solution obtained in step (8), dripping it onto both sides of the film sample to evenly cover it, and placing it in a forced air drying oven to evaporate the ethyl acetate, thereby finally obtaining a leak-proof liquid metal / melamine insulating thermal conductive film; The wind speed in the blast drying oven is 0.5m / s, the temperature is 60℃, and the time is 2 hours.

[0032] The density of the composite modified sponge is 0.0083g / cm 3 , thickness is 0.5cm.

[0033] The method for preparing the composite modified sponge comprises the following steps: (1) The melamine sponge was repeatedly rinsed with anhydrous ethanol and deionized water for 10 minutes, and then vacuum dried at 55°C for 2 hours to obtain a cleaned melamine sponge; (2) The silver nanowires are uniformly dispersed in deionized water to obtain a silver nanowire dispersion.

[0034] (3) immersing the cleaned melamine sponge in the silver nanowire dispersion, applying a pressure of 0.5 MPa to the cleaned melamine sponge, maintaining the pressure for 10 seconds, then releasing the pressure and maintaining it for 20 seconds, repeating the cycle for 5 times, then taking it out, placing it in a vacuum drying oven at 55° C. and vacuum drying it for 4 hours to obtain a melamine sponge composite material; (4) adding dopamine hydrochloride to the Tris solution, stirring and mixing to obtain a treatment solution; The melamine sponge composite material was added to the treatment liquid, ultrasonically dispersed for 10 minutes, the temperature was adjusted to 65°C, and after being sealed and immersed for 15 hours, it was taken out and then vacuum dried at 55°C for 4 hours to obtain a composite modified sponge.

[0035] The mass fraction of silver nanowires in the silver nanowire dispersion is 10wt%; The cleaning melamine sponge is immersed in the silver nanowire dispersion at a volume ratio of 1:10; The mixing ratio of dopamine hydrochloride and Tris solution is 1g:120mL; The volume ratio of melamine sponge composite material and treatment liquid is 1:5.

[0036] The gallium-indium alloy has a mass fraction of gallium of 75.5% and a mass fraction of indium of 24.5%.

[0037] The vacuum impregnation time was 4.5 hours, the vacuum degree was 0.1 Pa, and the temperature was 70°C.

[0038] The specific steps of mechanical sintering are as follows: the obtained multi-impregnation composite material is divided into four parts, and put into a tablet press for automatic pressing, each time the tablet press acts on one of the four parts, four times as one cycle, and a total of 10 cycles. The pressure is set to 1MPa, and the pressing time is 2s / time.

[0039] 20 μL / cm² 1%wt% PDMS / ethyl acetate solution was dripped onto both sides of the film sample.

[0040] Example 2

[0041] As a method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that the dipping in step 6 is repeated once.

[0042] Example 3

[0043] As a method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to an embodiment of the present invention, the only difference between this embodiment and Example 1 is that in the method for preparing the leakage-proof liquid metal / melamine insulating thermally conductive film, step 6 is repeated twice.

[0044] Example 4

[0045] As a method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to an embodiment of the present invention, the only difference between this embodiment and Example 1 is that in the method for preparing the leakage-proof liquid metal / melamine insulating thermally conductive film, step 6 is repeated 3 times.

[0046] Example 5

[0047] As a method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to an embodiment of the present invention, the only difference between this embodiment and Example 1 is that in the method for preparing the leakage-proof liquid metal / melamine insulating thermally conductive film, step 6 is repeated 4 times.

[0048] Example 6

[0049] As an embodiment of the present invention, a leakage-proof liquid metal / melamine insulating thermally conductive film and a preparation method thereof, the only difference between this embodiment and Embodiment 1 is that the ultrasonic cell pulverizer pulverization time is 2 minutes.

[0050] Example 7

[0051] As an embodiment of the present invention, a leakage-proof liquid metal / melamine insulating thermally conductive film and a preparation method thereof, the only difference between this embodiment and Embodiment 1 is that the ultrasonic cell pulverizer pulverization time is 6 minutes.

[0052] Comparative Example 1 As a method for preparing a thermally conductive film according to an embodiment of the present invention, the only difference between this comparative example and Example 5 is that mechanical sintering is not performed on the impregnated film.

[0053] Comparative Example 2 As a method for preparing a thermally conductive film according to an embodiment of the present invention, the difference between this comparative example and Example 5 is that in the mechanical sintering step of this comparative example, the sample is no longer divided into four parts, but is pressed as a whole piece, and is still pressed 10 times.

[0054] Comparative Example 3 As a method for preparing a thermally conductive film according to an embodiment of the present invention, the difference between this comparative example and Example 5 is that in this comparative example, the melamine sponge is not subjected to composite modification treatment.

[0055] Comparative Example 4 As a method for preparing a thermally conductive film according to an embodiment of the present invention, this comparative example is different from Example 5 in that the film sample is not subjected to PDMS coating treatment in this comparative example, that is, steps (8) and (9) are not performed.

[0056] test: The films prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were tested to verify the volume fraction before and after sintering, and the thermal conductivity before and after coating with PDMS. The test results are shown in Table 1: Among them, the test of thermal conductivity refers to GB / T 29313-2012

[0057] According to the data analysis of Examples 1 to 5 in Table 1, at least the following points can be obtained: 1. After each impregnation process, the volume fraction of the liquid metal attached to the composite modified melamine sponge was stably maintained at about 1%. Furthermore, after the pressing process, the volume fraction of the liquid metal showed a regular change trend. This phenomenon can be attributed to the binding force between the liquid metals and the binding force between the liquid metals and the silver nanowires. This binding force significantly exceeds the resilience of the melamine sponge itself, thereby prompting the liquid metal to effectively fill the gaps between the melamine sponges during the pressing process. Figure 3 shown.

[0058] 2. In order to further optimize the performance of the material, we coated a very thin layer of PDMS elastomer on the surface of the film, such as Figure 4It is worth noting that the thickness of this PDMS layer is only at the micron level and will not penetrate into the interior of the film, so it will hardly have a significant impact on the overall thermal conductivity of the material. In addition, this layer of PDMS provides external insulation for the film and can further prevent liquid metal leakage.

[0059] Correspondingly, a pressure test was performed on Example 5, as shown in the attached Figure 5 As shown, the film of Example 5 has no leakage of liquid metal under the pressures of 100 kPa, 300 kPa and 500 kPa.

[0060] This is not only due to the encapsulation of PDMS, but also because after the melamine sponge is mechanically sintered into a film, the liquid metal inside the film is more in the form of sheets rather than droplets. The sheet-like liquid metal has a larger lateral area and a smaller thickness due to its structural characteristics, and the contact area with the substrate surface is relatively larger. This larger contact area enhances the adhesion of the liquid metal to the film and silver nanowires through the surface tension effect, making it more stably fixed on the substrate and reducing the fluidity and leakage risk under the action of external forces.

[0061] The technical solution of the present invention balances the thermal conductivity of the material with the required elasticity, sealing and other properties to meet the comprehensive performance requirements in specific application scenarios.

[0062] 3. It can be seen from Examples 1, 6, and 7 in Table 1 that too short or too long an ultrasonic time will affect the distribution of the liquid metal on the skeleton. Figure 1 , 2 As shown, when the liquid metal dispersion is ultrasonically treated, as the ultrasonic time increases, the particle size of the liquid metal particles shows an overall downward trend. This is because the cavitation effect, shear effect and microjet effect of the ultrasonic wave act on the liquid metal particles, causing them to be subjected to strong impact and shear force, thereby causing the particles to be broken and refined. However, when the ultrasonic time reaches a certain level, the liquid metal droplets that are too small will re-agglomerate, causing certain fluctuations in the particle size distribution and an increase in the average particle size. Therefore, in multiple ultrasonic experiments, the inventors found that when the ultrasonic time is about minutes, the average particle size of the liquid metal droplets can be minimized, and the adsorption effect of the composite modified melamine sponge is the best.

[0063] 4. It can be seen from Example 1 and Comparative Examples 1 and 2 that the thermal conductivity of the melamine sponge that has not been sintered has not been significantly improved. The root cause of this phenomenon is the distribution of liquid metal particles on the melamine sponge skeleton - they show an uneven dispersion and fail to effectively build a continuous thermal conductive network; and the mechanical sintering step without block division of the melamine sponge will cause the sponge to bear an overall pressure, resulting in a reduction in the flow range of the liquid metal. Unlike block mechanical sintering, it can flow to the remaining directions in the sponge that are not under pressure, so that the liquid metal does not penetrate fully into the formed film, affecting the final thermal conductivity.

[0064] 5. It can be seen from Example 1 and Comparative Example 3 that the adsorption of liquid metal by melamine sponge without composite modification is only 80% of that after modification, and the thermal conductivity is also significantly reduced. This is because silver nanowires can form a strong interaction with the electron cloud on the surface of liquid metal due to their high free electron density; in addition, gallium in liquid metal usually forms a stable gallium oxide film, which can be firmly bonded to the silver surface through van der Waals force or chemical bond, thereby significantly improving the interface binding energy, thereby improving the adsorption of liquid metal by sponge. At the same time, silver nanowires also act as a bridge in the film structure, further optimizing the path connection, thereby significantly improving the thermal conductivity of the film.

[0065] Therefore, it can be concluded that the uniform dispersion of liquid metal particles on the melamine sponge skeleton and the construction of a continuous thermal conductive network through sintering treatment are the key to significantly improving the thermal conductivity of melamine sponge; the presence of flaky liquid metal inside the film increases its adhesion to the substrate, and it has a higher contact area and lower curvature, and is not easy to move under the action of gravity or external force. At the same time, the interaction between liquid metal and silver nanowires is also the key to ensure that the liquid metal does not leak; the presence of the PDMS protective layer not only provides insulation performance, but also further improves the film's anti-leakage ability and enhances its flexibility. This discovery has important guiding significance for guiding subsequent material design and preparation processes.

[0066] The above description is only an implementation mode of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film, characterized in that: The preparation method comprises the following steps: (1) Sponge matrix selection: The selected matrix is ​​a composite modified sponge; (2) Liquid metal selection: Gallium-Indium alloy; (3) Preparation of liquid metal / ethanol dispersion: mixing liquid metal and ethanol, and then placing them in an ultrasonic cell crusher for crushing to obtain a liquid metal / ethanol dispersion; The mass ratio of liquid metal to ethanol is 1:12-1:18, the ultrasonic power is 400W, and the treatment time is 2-6min; (4) Melamine sponge impregnation treatment: the composite modified sponge obtained in step (1) is placed in the liquid metal / ethanol dispersion obtained in step (3) at a volume ratio of 1:5 for impregnation treatment, and then taken out to obtain an impregnated sample; (5) Drying: Place the impregnated sample obtained in step (4) into a forced air drying oven for drying until the ethanol is completely evaporated; Among them, the wind speed in the blast drying oven is 0.5m / s, the temperature is 50℃, and the time is 0.5 hours; (6) Multiple impregnation: repeating steps (4) and (5) multiple times to obtain a multiple impregnation composite material; (7) Sintering of liquid metal components: mechanically sintering the multiple impregnation composite material obtained in step (6) to obtain a thin film sample; the mechanical sintering step is as follows: dividing the multiple impregnation composite material obtained into four parts, placing them into a tablet press for automatic pressing, wherein the tablet press acts on one part of the four parts each time, four times constitute one cycle, and a total of 10 to 12 cycles are performed; (8) Preparation of PDMS / ethyl acetate solution: PDMS: curing agent in a mass ratio of 9:1 were mixed evenly to obtain a preliminary mixture, and the preliminary mixture: ethyl acetate was poured into a centrifuge tube in a mass ratio of 1:9, and centrifuged and stirred for 5 minutes to prepare a 10% PDMS / ethyl acetate solution. The obtained solution was diluted 10 times to obtain a 1% PDMS / ethyl acetate solution; (9) Molding: The film sample obtained in step (7) is suspended on an aluminum mesh support, and the 1% PDMS / ethyl acetate solution obtained in step (8) is taken with a pipette and dripped onto both sides of the film sample to evenly cover the film sample, and then placed in a forced air drying oven to evaporate the ethyl acetate, thereby finally obtaining a leak-proof liquid metal / melamine insulating thermal conductive film; The air velocity in the blast drying oven is 0.5m / s, the temperature is 60℃, and the time is 2 hours; The method for preparing the composite modified sponge comprises the following steps: (1) The melamine sponge was repeatedly rinsed with anhydrous ethanol and deionized water for 10 minutes, and then vacuum dried at 55°C for 2 hours to obtain a cleaned melamine sponge; (2) uniformly dispersing the silver nanowires in deionized water to obtain a silver nanowire dispersion; the mass fraction of the silver nanowires in the silver nanowire dispersion is 10-13 wt %; (3) immersing the cleaned melamine sponge in the silver nanowire dispersion, applying a pressure of 0.5 MPa to the cleaned melamine sponge, maintaining the pressure for 10 seconds, then releasing the pressure and maintaining it for 20 seconds, repeating the cycle for 5 times, then taking it out, placing it in a vacuum drying oven at 55° C. and vacuum drying it for 4 hours to obtain a melamine sponge composite material; (4) Add dopamine hydrochloride to the Tris solution, stir and mix evenly to obtain a treatment solution; add the melamine sponge composite to the treatment solution, disperse it ultrasonically for 10 minutes, adjust the temperature to 65°C, keep it sealed and immersed for 15 hours, take it out, and then vacuum dry it at 55°C for 4 hours to obtain a composite modified sponge.

2. The method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to claim 1, characterized in that: The density of the selected composite modified sponge is 0.0080~0.0085g / cm 3 , thickness is 0.4~0.6cm.

3. The method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to claim 1, characterized in that: In step (8), the curing agent is tetraoxetane disulfide.

4. A method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to claim 41, characterized in that: The mass fraction of silver nanowires in the silver nanowire dispersion is 10-13wt%; The cleaning melamine sponge is immersed in the silver nanowire dispersion at a volume ratio of 1:10; The mixing ratio of dopamine hydrochloride and Tris solution is 1-1.2 g: 120 mL; The volume ratio of melamine sponge composite material and treatment liquid is 1:

5.

5. The method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to claim 1, characterized in that: The gallium-indium alloy has a mass fraction of gallium of 75.5% and a mass fraction of indium of 24.5%.

6. The method for preparing a non-leakage-proof liquid metal / melamine insulating thermally conductive film according to claim 1, characterized in that: The multiple repetitions of steps (4) and (5) are specifically repeated 1 to 4 times.

7. A method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to claim 81, characterized in that: The pressing pressure is 1 MPa, and the pressing time is 2 s / time.

8. The method for preparing a leakage-proof liquid metal / melamine insulating thermally conductive film according to claim 1, characterized in that: The amount of dripping on both sides of the film sample in step (9) is 20 μL / cm² respectively.

Citation Information

Patent Citations

  • A composite high thermal conductivity interlayer gasket and preparation method thereof

    CN114919252B

  • A two-dimensional graphene / liquid metal / PDMS composite film and its preparation method

    CN114940829B

  • Method for preparing low-voltage-driven electro-induced shape memory composite material

    CN107652465A

  • Liquid metal / aramid nano fiber heat-conducting composite material as well as preparation method and application thereof

    CN112759930A

  • Stretchable conductive composite material based on liquid metal and preparation method thereof

    CN113527862A